Factors Influencing Non-Performing Financing (NPF) In Sharia Banking - Hardana, Ali; Zein, Aliman Syahuri; Johanna, Anne; Avinash, Buschhaus (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
The risk of financing is the risk caused by the failure of the custom[1]ers to fulfill their obligations. Non-performing financing (NPF) is a representation of financing risk that is channeled and has a direct impact on bank profitability. The value of NPF tends to increase annually with a value that is already close to the maximum limit set by Bank Indonesia of 5 percent. This condition is able to lead to the inefficiency of the banking system and in the long run, will have an impact on the sustainability of the bank. Therefore, the analysis of NPF factors should be conducted as a preventive mea[1]sure and a risks controller of business activities. This research an[1]alyzes the factors influencing NPF at sharia banking (BUS) using a quarterly datafrom first quarter of 2012 until third quarter 2016. Method used in this research is panel data analysis. The result of analysis shows that the factors influencing NPF negatively and sig[1]nificantly are ratio of revenue sharing financing (RR), Return on ssets (ROA), inflation, Capital Adequacy Ratio (CAR) and Bank[1]size while Gross Domestic Product (GDP) and Operating Cost to Operating Income (BOPO) have a significant positive effect.